Species composition and diversity of Teak plantation in Karnaphuli range, Kaptai, Rangamati, Bangladesh - Abudllah, Rishad; Sarwar, Golam; Rahman, Mustafizur (Macedonian Journal of Ecology and Environment, 2020)
Teak (Tectona grandis L.f.) is a widely planted hardwood tree in Bangladesh, without considering its effects on native forest plants. To study the plant species composition and diversity in a Teak plantation a quantitative vegetation inventory was performed using transect method in the Karnaphuli range of Kaptai reserve forest, Rangamati district, Bangladesh during 2015-2017. The size of the quadrates was 20×20m, 5×5m and 1×1m for trees, shrubs and herbs respectively, to get density, abundance, relative density, relative frequency, basal area, etc. The species composition is presented by density and frequency; the dominancy of species is presented by Importance Value Index; the species diversity and concentration of dominance is presented by Shannon’s index of diversity. A total of 78 plant species, including 34 trees, 19 shrubs and 25 herbs belonging to 40 families and 70 genera were noticed during the study. The Tectona grandis among trees, Lantana camera in shrubs and Heliotropium indicum in herbs were found to be the dominant species. The family Euphorbiaceae among trees, Rubiaceae and Verbenaceae among shrubs and Araceae among herbs were observed to be the dominant families. Tree species showed contagious whereas shrubs and herb species showed random to contagious distribution pattern. The Shannon’s diversity index for trees, shrubs and herbs were 1.486, 2.624 and 2.944, respectively. This study provides in-depth information about the plant species phytosociological parameters and diversity indices of Teak plantation, which is essential to make conservation strategies for the protection and development of plant biodiversity.